2014
DOI: 10.1371/journal.pone.0091094
|View full text |Cite
|
Sign up to set email alerts
|

Convallatoxin, a Dual Inducer of Autophagy and Apoptosis, Inhibits Angiogenesis In Vitro and In Vivo

Abstract: Autophagy and apoptosis are important processes that control cellular homeostasis and have been highlighted as promising targets for novel cancer therapies. Here, we identified convallatoxin (CNT), isolated from Antiaris toxicaria, as a dual inducer of autophagy and apoptosis. CNT exerts cytotoxic effects on a number of cancer and normal cell lines and induces apoptosis by increasing caspase-3 and poly ADP ribose polymerase (PARP) cleavage. Moreover, dose- and time-dependent autophagic activity was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…This modified form, termed LC3B-II, is involved in the elongation of the phagophore. 28 However, LC3B-II is also degraded inside the lysosomes or deconjugated by ATG4. 29 Therefore, in order to measure autophagic flux, through 3-AWA (subtoxic doses)-induced autophagy, the LysoTraker Green dye was employed to characterize acidic spherical organelles formed at the onset of autophagy.…”
Section: A Lower Concentration Of 3-awa Induces Autophagy In Prostatementioning
confidence: 99%
“…This modified form, termed LC3B-II, is involved in the elongation of the phagophore. 28 However, LC3B-II is also degraded inside the lysosomes or deconjugated by ATG4. 29 Therefore, in order to measure autophagic flux, through 3-AWA (subtoxic doses)-induced autophagy, the LysoTraker Green dye was employed to characterize acidic spherical organelles formed at the onset of autophagy.…”
Section: A Lower Concentration Of 3-awa Induces Autophagy In Prostatementioning
confidence: 99%
“…It is not the first time that both apoptosis and autophagy have been induced by the same compound. The simultaneous induction of these processes has been reported, e.g., for a curcumin analog against hepatocellular carcinoma cells (27) and by convallatoxin, an angiogenesis inhibitor (28). This is the first time programmed cell death has been shown to occur in Paracoccidioides; however, it has already been described in other unicellular organisms, including yeast cells and bacteria (29,30).…”
Section: Discussionmentioning
confidence: 90%
“…(Braga et al 1996) was evaluated for the first time in this study. CON, isolated from Convallaria majalis L., has been reported to possess cytotoxic effects against several cancer cells (Juncker et al 2011;Yang et al 2014). In order to investigate the cytotoxic effects of these compounds in other cancer cells, human non-small cell lung cancer (NSCLC, A549), human rhabdomyosarcoma RD, human colon carcinoma HCT-8 and human prostate carcinoma LNcAP cell lines were selected.…”
Section: Dgx and Con Reduced Cancer Cells Proliferationmentioning
confidence: 99%
“…In A549 cell line, the most sensitive cell line for both compounds, the IC 50 values were 12.34 and 11.03 nM, respectively, after 48 h. CON was identified as a potent cardenolide in different reports, with IC 50 values at nM concentrations, as herein observed. Its anti-proliferative effects were evaluated in colorectal cancer (HT29, HCT116 and CC20) (Felth et al 2009), non-small cell lung cancer (NIH-H460 and A549) (Liu, Tang, et al 2013;Yang et al 2014), glioblastoma (U87MG), cervical cancer (HeLa), liver carcinoma (HepG2) and fibrosarcoma (HT1080) (Yang et al 2014) human cell lines. It was also shown that CON caused a dual induction of apoptosis and autophagy in HeLa cells (Yang et al 2014).…”
Section: Dgx and Con Reduced Cancer Cells Proliferationmentioning
confidence: 99%
See 1 more Smart Citation